Comparing the antimicrobial properties of graphene oxide silver nanoparticles as a root canal irrigant: A randomized controlled trial - Annapoorani Sevagaperumal; M K Gayathri Lakshmi; R S Rathna Piriyanga; S Swathi Priyadharshini; A Azhagu Abirami; I Anand Sherwood (Wolters Kluwer Medknow Publications, 2024)
Aim: The current study aimed to compare and evaluate the antimicrobial efficacy of graphene oxide (GO) silver nanoparticle (AgNp) as root canal irrigant (RCI) with other RCIs in maxillary anterior teeth with necrotic pulp. Methods: The GO AgNp RCI was synthesized following modified Turkevich method and subsequent physicochemical characterization was carried out. Sample size was calculated to be 44 and divided into four groups. Following initiation of root canal treatment, preirrigation aerobic and anaerobic samples were collected in suitable medium and the same was done after completion of irrigation adapting the proposed protocol. Further, culture of aerobic and anaerobic samples was done accompanied by determination of bacterial viability count. From the obtained results, statistical analysis was performed and analysis of variance with post hoc was used to compare the antibacterial efficacy between the four irrigants. Results: The statistical analysis ended up with a significant difference in antibacterial properties between GO AgNps and normal saline, 2% chlorhexidine (P < 0.01) against both aerobic and anaerobic organisms. 2.5% sodium hypochlorite and GO AgNp irrigant showed a similar result against aerobic organisms (P = 1.00) while 2.5% sodium hypochlorite was slightly effective against anaerobic organisms (P = 0.83). The bacterial viability counts also showed results in accordance with culture results. Conclusion: From the above results, it can be concluded that the GO AgNp irrigant is an effective biocompatible antimicrobial agent, comparable to that of 2.5% sodium hypochlorite and superior to 2% chlorhexidine and normal saline.